2016
DOI: 10.1016/j.watres.2016.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Changes of resistome, mobilome and potential hosts of antibiotic resistance genes during the transformation of anaerobic digestion from mesophilic to thermophilic

Abstract: a b s t r a c tThis study aimed to reveal how antibiotic resistance genes (ARGs) and their horizontal and vertical transfer-related items (mobilome and bacterial hosts) respond to the transformation of anaerobic digestion (AD) from mesophilic to thermophilic using one-step temperature increase. The resistomes and mobilomes of mesophilic and thermophilic sludge were investigated using metagenome sequencing, and the changes in 24 representative ARGs belonging to three categories, class 1 integron and bacterial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(73 citation statements)
references
References 59 publications
4
69
0
Order By: Relevance
“…and , types of ARGs (Wu et al, 2016;Shi et al, 2013), and operating parameters (Tian et al, 2016). The investigation on the removal of ARGs in different treatment units of four wastewater treatment plants showed that the biological treatment unit played the most important role in ARGs removal (1.2e1.8 orders of magnitude), and followed by UV disinfection while primary physical treatment units could hardly remove any ARGs (Wen et al, 2016).…”
Section: Proliferation Of Args Through Various Treatment Units In Thementioning
confidence: 99%
“…and , types of ARGs (Wu et al, 2016;Shi et al, 2013), and operating parameters (Tian et al, 2016). The investigation on the removal of ARGs in different treatment units of four wastewater treatment plants showed that the biological treatment unit played the most important role in ARGs removal (1.2e1.8 orders of magnitude), and followed by UV disinfection while primary physical treatment units could hardly remove any ARGs (Wen et al, 2016).…”
Section: Proliferation Of Args Through Various Treatment Units In Thementioning
confidence: 99%
“…intI1, integrase of class 1 integrons) are often involved (Stalder et al, 2012). Class 1 integrons routinely contain mobile antibiotic and biocideresistance genes (Stokes and Gillings, 2011) and are described as part of the "mobilome" (Tian et al, 2016). For example, class 1 integrons were validated as a proxy for anthropogenic ARG inputs to the Thames River basin by Amos et al (2015), who modeled various contributing factors impacting environmental resistome presence and determined that wastewater effluent was the major source.…”
Section: Presence and Transfer Of Relevant Genes Within Environmentalmentioning
confidence: 99%
“…Pyrosequencing combines standard PCR and sequencing by synthesis to rapidly determine the sequence of a target DNA region; it has been extensively used for the detection of bacterial resistance genes and bacterial community composition (Tang et al, 2016; Tian et al, 2016). This technique has been used to perform mutation analysis of bla SHV to resolve heterogeneous sequences in clinical isolates of K. pneumoniae containing more than one SHV variant (Haanperä et al, 2008).…”
Section: Detectionmentioning
confidence: 99%